PENGEMBANGAN MODUL DIGITAL INTERAKTIF BERBASIS FLIPBOOK MATA KULIAH MANAJEMEN PAUD - Tini Adiatma; Paskha Marini Thana (JURNAL PENDIDIKAN, 2022)
Early childhood education management should be considered to make sure the educational process going well. Early childhood education management in Indonesia there is still some problem occur. This problem also can be solved by prepare human resource that capable to handle the management process in early childhood education institutions. In higher education, this topic became a course that should be mastering by student of early childhood teacher education. Modul can be a media that support the educational process. This research aims to develop flipbook-based digital interactive module in management of early education course. This research conduct by research and development method. The result of this research is a flipbook-based digital interactive module on early childhood education management. This module developed using heyzine.com, canva.com, wordwall.net, and google docs to make this module more interactive and accessible to everyone. This module gets a good response from media expert, material expert, and user which is higher education students.